Effects of social participation patterns and living arrangement on mental health of Chinese older adults: A latent class analysis - Chen, Jieyao; Zeng, Yanbing; Fang, Ya (Frontiers in Public Health, 2022)
Objectives The purpose of this study was to discover patterns of social participation among Chinese older individuals, investigate the links between these patterns and their living arrangements and mental health, and connect these patterns to their background characteristics. Methods Data were drawn from the 2014 and 2018 waves of Chinese Longitudinal Healthy Longevity Survey (CLHLS) from 2537 Chinese elders aged 60 years and over at the baseline. Latent class analysis was used to determine the patterns of social participation. Multinomial logistic regression was used to explore the relationship between patterns of social participation and the sociodemographic and health characteristics of older adults. Binary logistic regression was used to explore the differences and associations between these categories and living arrangement on mental health status, represented by positive and negative emotions. Results Three patterns of social participation were identified: Low activity (17.5%, n = 443); Moderate activity (36.2%, n = 1,176); and High activity (46.3%, n = 918). At baseline, these patterns were significantly associated with mental health status. Positive and negative emotions were much better in the High activity group than in the other two groups (OR = 1.36, 95% CI = 1.05–1.76 and OR = 1.50, 95% CI = 1.16–1.93). Living arrangement only significantly affected negative emotions (OR=1.25, 95% CI = 1.02–1.53). Age, gender, education, marital status, self-rated health, and activities of daily living limitations all affected social participation patterns. Conclusions The patterns of social participation and living arrangement of Chinese older adults are significantly associated with mental health. Population-tailored interventions may help liberate older adults from domestic labor and improve social participation. Moreover, family support can decrease negative emotions' damage in old age thus promoting health.